Restoration of the condition which has been except infringement of the right, as an effective method of protection: distribution of administrative jurisdiction from civil and economic activity - Zhuk, Andrii (Actual problems of law (Aktual'ni problemi pravoznavstva), 2018)
The article is devoted to the analysis of the legal nature and peculiarities of the application of the restoration of the situation that existed before the violation of law, and the resumption of law as an effective means of protecting the rights of citizens. Conditions and peculiarities of the application of these methods of protection, as well as examples of judicial practice, are considered.